Review of Diagnostic Procedures and Approaches to Infectious Causes of Reproductive Failures of Cattle in Australia and New Zealand - Reichel, Michael P.; Wahl, Lloyd C.; Hill, Fraser I. (Frontiers in Veterinary Science, 2018)
Infectious causes of reproductive failure in cattle are important in Australia and New Zealand. Neospora caninum ranks highly as an important cause of reproductive wastage along with fungal and bacterial infections. Leptospirosis in cattle is largely controlled by vaccination, while Campylobacter and Tritrichomonas infections occur at low rates. In both countries, Bovine Viral Diarrhoea virus infection rates as the second most economically important disease of cattle and one that also has effect on reproduction. This review will discuss the infectious causes of reproductive losses present and absent in both countries and an effective pathway to a diagnosis.